EMPLOYEE PERSPECTIVE ANALYSIS OF TRADE UNIONISM IN PUBLIC SECTOR BANKS IN KERALA - Shindu Varghese and Malarmati K. 2 (Sai Om Journal of Commerce & Management, 2015)
Now trade union has emerged over the period as a major institutional mechanism for resolving conflicts of interest between the workers and the employers. A trade union serves as a link between employers and workers so as to develop mutual understanding and co-operation between the two sides. They can play a vital role in avoiding conflicts by collective talks and collective bargaining. This paper examines the working of the Trade Unions in banking sector and to evaluate the extent of satisfaction of employees regarding the function of the organisation to the benefit of the employees and to the organisation as a whole.